2021
DOI: 10.3389/fmars.2021.668325
|View full text |Cite
|
Sign up to set email alerts
|

Approach to the Functional Importance of Acropora cervicornis in Outplanting Sites in the Dominican Republic

Abstract: Coral restoration has been recognized as an increasingly important tool for coral conservation in recent years. In the Caribbean, the endangered staghorn coral, Acropora cervicornis has been studied for restoration for over two decades with most studies focusing on evaluating simple metrics of success such as colony growth and survivorship in both nurseries and outplanted sites. However, for reef restoration to aid in the recovery of ecological function in outplanted sites, there is a need to measure the funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 60 publications
0
7
0
Order By: Relevance
“…and Acathurus sp. (Shantz et al, 2017;Calle-Triviño et al, 2021). Despite, the highest contributions of grunts and herbivorous fishes (surgeonfishes and parrotfishes) in both study sites our results suggest that there is a good chance of using these species to enhance research and may be considered in the context of restoration both structurally and functionally.…”
Section: Discussionmentioning
confidence: 74%
“…and Acathurus sp. (Shantz et al, 2017;Calle-Triviño et al, 2021). Despite, the highest contributions of grunts and herbivorous fishes (surgeonfishes and parrotfishes) in both study sites our results suggest that there is a good chance of using these species to enhance research and may be considered in the context of restoration both structurally and functionally.…”
Section: Discussionmentioning
confidence: 74%
“…For example, a large-scale coral restoration project in Seychelles demonstrated a positive correlation between the presence of coral recruits and juveniles and outplanted corals (Montoya-Maya et al 2016). Recent research on single species outplanting in the Caribbean showed greater ecological functions in restored areas using a complex assessment of ecological indicators (Calle-Triviño et al 2021). For the Maldives, comparable studies date back to the 1990s, where whole colonies were transplanted to artificial substrates which were then rapidly colonized by fish.…”
Section: Discussionmentioning
confidence: 99%
“…Global climate action, the establishment of marine protected areas, sustainable fishing practices, and effective management of water systems all are critical tools for reef recovery. Alongside these efforts, coral restoration has the potential to further help recovery of damaged or depleted reefs (Wilkinson and Souter, 2008;Young et al, 2012) and there is increasing recognition that it should play a strategic role in protecting critical ecosystem services (Abelson, 2006;Edwards, 2010;Chamberland et al, 2015;Schopmeyer et al, 2017;Calle-Triviño et al, 2018;Calle-Triviño et al, 2021). Numerous reef restoration projects have been developed in recent years to alleviate bottlenecks of recovery for Caribbean coral communities (Bayraktarov et al, 2020), leading to numerous advancements in techniques to growing and reproducing corals in aquarium settings.…”
Section: Reef Restoration Bottlenecks In the Caribbeanmentioning
confidence: 99%